NHC‐stabilized Silicon(II) Halides: Reactivity Studies with Diazoalkanes and Azides1. Issue 22 (7th October 2016) - Arz, Marius I.; Hoffmann, David; Schnakenburg, Gregor; Filippou, Alexander C.
Abstract : Detailed studies of the reactivity of the NHC‐stabilized (NHC = N‐heterocyclic carbene) silicon(II) halides SiI2 (Idipp) (1 ) and SiClR(IMe4 ) (2 ‐Trip : R = Ar Trip ;2 ‐Mes : R = Ar Mes ) towards diazoalkanes and azides are presented (Idipp = C[N(C6 H3 –2, 6‐ i Pr2 )CH]2, IMe4 = C[N(Me)CMe]2, Ar Trip = C6 H3 ‐2, 6‐Trip2, Ar Mes = C6 H3 ‐2, 6‐Mes2, Trip = C6 H2 ‐2, 4, 6‐ i Pr3, Mes = C6 H2 ‐2, 4, 6‐Me3 ). Treatment of1, 2 ‐Trip, and2 ‐Mes with the diazoalkanes ( p ‐Tol)2 CN2 ( p ‐Tol = C6 H4 ‐4‐Me) and Ar Mes CHN2 afforded the NHC‐stabilized silazines SiI2 N2 C( p ‐Tol)2 (Idipp) (3 ) and SiCl R N2 CH(Ar Mes )(IMe4 ) (4 ‐Trip : R = Ar Trip, 4 ‐Mes : R = Ar Mes ) as orange to yellow solids, respectively. No N2 elimination from the diazoalkanes was observed in these reactions. In comparison, the reactions of1 or2 ‐Trip with the covalent azides MesN3 or Me3 SiN3, yielded after N2 elimination the yellow to colorless NHC‐stabilized silaimines SiI2 (NMes)(Idipp) (5 ), Si(Ar Trip )Cl(NMes)(IMe4 ) (6 ) and Si(Ar Trip )(N3 )(NSiMe3 )(IMe4 ) (7 ), respectively. All compounds were characterized by elemental analyses, FT‐IR and multinuclear magnetic resonance spectroscopy. Moreover, the molecular structures of4 ‐Mes, 5, 6, and7 were determined by single‐crystal X‐ray diffraction analyses. Abstract :